PENGARUH PENGHASILAN, KESADARAN, DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) (Studi Kasus di Dusun Kaliurang Barat, Desa Hargobinangun Tahun 2015) - Nasirin Nasirin (JURNAL EKOBIS DEWANTARA, 2018)
The objectives of this research are to find out whether one’s income, awareness, and understanding as a tax payer influence his obedience to pay his land and building taxes in West Kaliurang, Hargobinangun village, to find out whether the income of a tax payer influences his obedience to pay his land and building taxes in West Kaliurang, Hargobinangun village, to find out whether the awareness of a tax payer influences his obedience to pay his land and building taxes in West Kaliurang, Hargobinangun village, and (d) to find out whether one’s understanding as a tax payer influences his obedience to pay his land and building taxes in West Kaliurang, Hargobinangun village. The sample of this research was taken by employing non-probability method using purposive sample technique. The non-probability method is the technique of taking research sample that does not give the same chance/opportunity to each element or population member to be selected as the sample (Sugiyono, 2008). The hypothesis in this research was tested using a linier regression analysis. It was used to test the influence of the dependent variable (Y) and independent variables (X). This research employed the equation of double regression: Y = α +β1X1 + β2X2 + β3X3. Y = 1,354 +0,034X1 + 0,282X2 +0,376X3. Based on the data analysis, it is concluded there is a negative influence of the tax payer’s income variable on his obedience to pay his land and building taxes, there is a positive influence of the tax payer’s awareness variable on his obedience to pay his land and building taxes, and there is a positive influence of one’s understanding as a tax payer variable on his obedience to pay his land and building taxes.